Combined Assessment of Diffusion Parameters and Cerebral Blood Flow Within Basal Ganglia in Early Parkinson’s Disease - Pelizzari, Laura; Laganà, Maria M.; Di Tella, Sonia; Rossetto, Federica; Bergsland, Niels; Nemni, Raffaello; Clerici, Mario; Baglio, Francesca (Frontiers in Aging Neuroscience, 2019)
Diffusion tensor imaging (DTI) is a sensitive tool for detecting brain tissue microstructural alterations in Parkinson’s disease (PD). Abnormal cerebral perfusion patterns have also been reported in PD patients using arterial spin labeling (ASL) MRI. In this study we aimed to perform a combined DTI and ASL assessment in PD patients within the basal ganglia, in order to test the relationship between microstructural and perfusion alterations. Fifty-two subjects participated in this study. Specifically, twenty-six PD patients (mean age [SD]=66.7[8.9] years, 21 males, median [IQR] Modified Hoehn and Yahr = 1.5 [1-1.6]) and twenty-six healthy controls (HC, mean age [SD]=65.2[7.5], 15 males) were scanned with 1.5T MRI. Fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD) maps were derived from diffusion-weighted images, while cerebral blood flow (CBF) maps were computed from ASL data. After registration to Montreal Neurological Institute standard space, FA, MD, AD, RD and CBF median values were extracted within specific regions of interest: substantia nigra, caudate, putamen, globus pallidum, thalamus, red nucleus and subthalamic nucleus. DTI measures and CBF were compared between the two groups. The relationship between diffusion parameters and CBF was tested with Spearman’s correlations. False discovery rate (FDR)-corrected p-values lower than 0.05 were considered significant, while uncorrected p-values < 0.05 were considered a trend. No significant FA differences were observed. AD was significantly increased in PD patients compared with HC in the putamen (p=0.039, pFDR=0.035). No significant CBF differences were found between PD patients and HC. Diffusion parameters were not significantly correlated with CBF in the HC group, while a significant correlation emerged for PD patients in the caudate nucleus, for all DTI measures (with FA: r=0.543, pFDR=0.028; with MD: r=-0.661, pFDR=0.002; with AD: r=-0.628, pFDR=0.007; with RD: r=-0.635, pFDR=0.003). This study showed that DTI is a more sensitive technique than ASL to detect alterations in the basal ganglia in the early phase of PD. Our results suggest that, although DTI and ASL convey different information, a relationship between microstructural integrity and perfusion changes in the caudate may be present.